Let it be - Public Television Service ([Taiwan : Public Television Service], 2004)
This documentary film, Let It Be, records the everyday labor and lives of three elderly rice farmers in Houbi Township, in the heart of Taiwan's rice-producing country. It depicts their lifestyles that have changed little over the last half-century, and how they must toil and shed a bead of sweat for each grain they produce. It observes their toils and their approach to life, enabling viewers to appreciate the wisdom that imbues their lives, and the fascinating dynamics of their relationships with each other, their animals, gods, the weather, and the land
DVD Format
Subtitles in Tradisional Chinese, English, Francais and Espanol
Keywords: Rice farmers -- Taiwan; Rice -- Processing